Determination and analysis of the complete mitochondrial genome of Barilius barila (Cypriniformes: Danionidae: Chedrinae). Issue 11 (2nd November 2022) - Chen, Xiao Jiang; Song, Lin; Song, Yang; Wang, Quan
Abstract: Cyprinid fish Barilius barila found in the Irrawaddy water system is a valuable fishery resource and has been listed as Least Concern by the IUCN. This study determined the complete mitochondrial genome of B. barila from Yunnan, China, for the first time. Circular molecule of B. barila mitogenome was sequenced to be 16, 560 bp in length, with the typical gene structure of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and two noncoding areas (control region and the origin of L-strand replication). Overall nucleotides composition appeared to be 27.5% A, 24.8% T, 19.2% G, and 28.6% C, with a slight AT (52.3%) bias. The topology of the phylogenetic tree showed that B. barila was well grouped with Opsarius caudiocellatus, and clustered together with the genus Opsarius instead of Barilius, revealing that it was more reasonable for Barilius barila to belong to Opsarius rather than Barilius .